Recent Developments in Molecular Dynamics Simulations of Fluorescent Membrane Probes - Loura, Luís M. S. (2011)
Due to their sensitivity and versatility, the use of fluorescence techniques in membrane biophysics is widespread. Because membrane lipids are non-fluorescent, extrinsic membrane probes are widely used. However, the behaviour of these probes when inserted in the bilayer is often poorly understood, and it can be hard to distinguish between legitimate membrane properties and perturbation resulting from probe incorporation. Atomistic molecular dynamics simulations present a convenient way to address these issues and have been increasingly used in recent years in this context. This article reviews the application of molecular dynamics to the study of fluorescent membrane probes, focusing on recent work with complex design fluorophores and ordered bilayer systems.